A comparative study of pure and silver-enhanced graphene antennas for fat-intrabody communication - Subramaniam, Sree Aran; Asan, Noor Badariah; Abd. Aziz, Mohamad Zoinol Abidin (2024)
This paper presents the design and comparative study of two implant antennas utilizing graphene material for fat-intrabody communication (fat-IBC) in the 5.8 GHz Industrial, Scientific, and Medical (ISM) band. Both antennas use pure graphene and silver-enhanced graphene as radiating elements, fabricated on a Taconic TLY-3 substrate. Copper-conducting elements were used as the substitute conductive material in CST Microwave Studio simulation for the optimized designs. These antennas were then measured in a fat-tissue-equivalent phantom model, and the S11reflection coefficients were recorded. These results show that the silver-enhanced graphene antenna has better performance in conductivity and resonance sharpness compared with the pure graphene antenna, which can be applied for the fat-IBC system.